L’enseignement des sujets sensibles en contexte de diversités - Alexis Poirier-Saumure; Saaz Taher; Nordin Lazreg (Communication)
This article aims to analyze the emotional aspects central to the ethical, political, social and educational tensions (Hirsch & Moisan, 2022) related to the teaching of sensitive subjects at the post-secondary level and the processes by which affects can structure the relationship to diversity and guide teaching strategies. Based on testimonials from faculty and students gathered as part of a research project on strategies for teaching sensitive topics in the context of diversity, we aimed to improve our understanding of the effects of numerous emotional registers in the classroom and their influence on teaching approaches related to diversity and sensitivities.